Factors Influencing Students' Entrepreneurial Intention: Examining the Role of Entrepreneurship Education and Entrepreneurial Self-Efficacy - Zaid, Zaid; Wahyuningsih, Adityas; Pratondo, Katon; Ramadhan, Rizqa Nuzul; Al Bahy, Mahbub Pasca (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This research aims to examine and predict the factors influencing students' entrepreneurial interest by referring to perceptions of entrepreneurship education and entrepreneurial self-efficacy. Through quantitative methods with a cross-sectional approach, this research involving 256 respondents resulted in students' entrepreneurial intention because they were influenced by entrepreneurship education and entrepreneurial self-efficacy. Even though the influence of entrepreneurial self-efficacy is higher than that of entrepreneurship education, it cannot be underestimated because apart from self-efficacy, entrepreneurship education also has a positive and significant influence on students' entrepreneurial intentions. From these results, the proposal put forward in this research is that universities must be able to improve entrepreneurship education and student self-efficacy to become entrepreneurs. Recommendations for further research are also recommended in this study.